Eternal protection in grid graphs - Goldwasser, John L.; Klostermeyer, William F.; Mynhardt C.M. (Utilitas Mathematica, 2013)
Eternal domination of a graph requires the vertices of the graph to be protected, against infinitely long sequences of attacks, by guards located at vertices, with the requirement that the configuration of guards induces a dominating set at all times. We present results and conjectures for grid graphs for some variations on this problem.